Retinoic Acid Signaling: A New Piece in the Spoken Language Puzzle - van Rhijn, Jon-Ruben; Vernes, Sonja C. (Frontiers in Psychology, 2015)
Speech requires precise motor control and rapid sequencing of highly complex vocal musculature. Despite its complexity, most people produce spoken language effortlessly. This is due to activity in distributed neuronal circuitry including cortico-striato-thalamic loops that control speech-motor output. Understanding the neuro-genetic mechanisms that encode these pathways will shed light on how humans can effortlessly and innately use spoken language and could elucidate what goes wrong in speech-language disorders. FOXP2 was the first single gene identified to cause speech and language disorder. Individuals with FOXP2 mutations display a severe speech deficit that also includes receptive and expressive language impairments. The underlying neuro-molecular mechanisms controlled by FOXP2, which will give insight into our capacity for speech-motor control, are only beginning to be unraveled. Recently FOXP2 was found to regulate genes involved in retinoic acid signaling and to modify the cellular response to retinoic acid, a key regulator of brain development. Herein we explore the evidence that FOXP2 and retinoic acid signaling function in the same pathways. We present evidence at molecular, cellular and behavioral levels that suggest an interplay between FOXP2 and retinoic acid that may be important for fine motor control and speech-motor output. We propose that retinoic acid signaling is an exciting new angle from which to investigate how neurogenetic mechanisms can contribute to the (spoken) language ready brain.